Insights and Opportunities: Evaluating a University Teaching and Learning Grants Program - Heather Jamniczky; Mohana Mukherjee; Rachel Stewart; Andrew Mardjetko; Rahim Pira; Natasha Kenny (Canadian Journal for the Scholarship of Teaching and Learning)
We describe a detailed program evaluation for a University-wide teaching and learning grants program at a Canadian research-intensive university. This work was designed to determine if the program is driving the types of changes in practice it was designed to support. We administered a survey that included yes/no response and Likert-scale questions to assess supports provided, outcomes, challenges, and impact of the grants program; and a series of open-ended questions inviting participants to share qualitative narratives describing their perceptions of the program and its effects. Thematic analysis of the survey responses revealed that the grants program provides tremendous value in strengthening scholarly communities and fosters wide ranging benefits to learners and teachers through ripple effects that extend well beyond the stated goals of the program. The engagement of students as partners in scholarly work and the development of local cultures and conversations around the scholarship of teaching and learning generated exciting new opportunities. The program supported innovative teaching strategies and deep engagement in teaching and learning, and provided opportunities for presentation, publication, and support from national funding bodies. It is clear that our institutional teaching and learning grants program is key to fostering a scholarly environment on our campus that benefits the entire community.